Identification of Insecticidal Constituents from the Essential Oil of Valeriana jatamansi Jones against Liposcelis bostrychophila Badonnel - Xin Chao Liu; Ligang Zhou; Zhi Long Liu (Journal of Chemistry)
The aim of this research was to determine chemical composition and insecticidal activities of the essential oil of Valeriana jatamansi Jones roots against booklice, Liposcelis bostrychophila Badonnel, and to isolate insecticidal constituents from the oil. Essential oil of V. jatamansi was obtained by hydrodistillation and analyzed by GC-MS. A total of 27 components in the essential oil were identified. The major compounds were patchoulol (24.3%), α-bulnesene (13.8%), isovaleric acid (12.9%), α-guaiene (8.7%), and 3-methylvaleric acid (8.4%). Based on bioactivity-guided fractionation, isovaleric acid, 3-methylvaleric acid, and patchoulol were isolated and identified as the active constituents. The essential oil exhibited contact toxicity against L. bostrychophila with an LC50 value of 236.4 μg/cm2. Patchoulol (LC50 = 61.35 μg/cm2) exhibited stronger acute toxicity than 3-methylvaleric acid (LC50 = 210.69 μg/cm2) against the booklice. The essential oil also possessed fumigant toxicity against L. bostrychophila with an LC50 value of 6.0 mg/L, while 3-methylvaleric acid and isovaleric acid had LC50 values of 5.53 mg/L and 5.67 mg/L against the booklice, respectively. The results indicated that the essential oil and its constituent compounds have potential to develop into natural insecticides or fumigants for control of insects in stored grains.